Pemanfaatan Media Pembelajaran Busy Book Flanel Untuk Mengenalkan Matematika Permulaan Pada Anak Usia Dini Di Taman Kanak-Kanak Islam Terpadu Al-Azka Kota Jambi - Andik Rahmatiah; Dhea Afrilia; Septiana; Nadilla Monica; Akhmad Fikri Rosyadi (CV. ITTC INDONESIA, 2024)
Abstract Early mathematics is a very important and basic ability for children that needs to be developed in order to equip children for their future lives. However, the reality is that there are many demands and expectations from parents about their children's ability to be able to count. The application of interesting media is the main determining factor when learning numeracy concepts. One of the media used to increase students' numeracy skills is the use of busy books. This activity is about the use of flannel busy book learning media to introduce early mathematics to early childhood at Al-Azka IT Kindergarten Jambi City. The concept of introducing early mathematics to early childhood includes: 1) Introducing the concept of numbers to children, 2) Developing concept of numbers, 3) Introducing geometric shapes, 4) Sorting objects based on size, 5) Ordering number symbols. The aim of this community service activity is to assist parents and teachers in introducing beginning mathematics by using busy books for early childhood at the Al-Azka Integrated Islamic Kindergarten, Jambi City. The method used in Community Service (PKM) activities is the Service Learning (SL) method. This method plays an important role in independence, especially student independence. The Community Service (PKM) carried out is the implementation of the use of the busy book method in introducing early childhood mathematics to early childhood students at the Al-Azka Integrated Islamic Kindergarten, Jambi City. The results of this Community Service (PKM) Use of busy books can improve early mathematics skills in early childhood. Therefore, through this service, it is hoped that teachers and parents can introduce young children to early mathematics starting from the concept of numbers 1-10, symbols for numbers 1-10 and geometric shapes and can create and utilize creative and innovative learning media using the busy book method.